2020
DOI: 10.3390/biom10010160
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Models for the Investigation of Potential Drugs Against Schizophrenia

Abstract: Schizophrenia (SZ) is a complex psychiatric disorder characterized by positive, negative, and cognitive symptoms, and is not satisfactorily treated by current antipsychotics. Progress in understanding the basic pathomechanism of the disease has been hampered by the lack of appropriate models. In order to develop modern drugs against SZ, efficient methods to study them in in vitro and in vivo models of this disease are required. In this review a short presentation of current hypotheses and concepts of SZ is fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 153 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…It plays a key role in neuronal synapse formation, neuron migration and synaptic plasticity. Numerous biological studies have confirmed the role of DISC1 in early neurodevelopment and synaptic regulation (Brandon & Sawa, 2011; Koszla, Targowska‐Duda, Kedzierska, & Kaczor, 2020; Lee et al, 2011; Millar et al, 2000; Soares, Carlyle, Bradshaw, & Porteous, 2011; St Clair et al, 1990). Following the discovery of this gene, researches using model organisms to examine the biological functions of DISC1 have achieved fruitful results.…”
Section: Genetically Engineered Animal Experimental Modelsmentioning
confidence: 93%
“…It plays a key role in neuronal synapse formation, neuron migration and synaptic plasticity. Numerous biological studies have confirmed the role of DISC1 in early neurodevelopment and synaptic regulation (Brandon & Sawa, 2011; Koszla, Targowska‐Duda, Kedzierska, & Kaczor, 2020; Lee et al, 2011; Millar et al, 2000; Soares, Carlyle, Bradshaw, & Porteous, 2011; St Clair et al, 1990). Following the discovery of this gene, researches using model organisms to examine the biological functions of DISC1 have achieved fruitful results.…”
Section: Genetically Engineered Animal Experimental Modelsmentioning
confidence: 93%
“…It is not only that normal structure of the human brain is a fascinating topic for research, but the diseased brain is even more exciting. It has been self-evident that complex psychiatric disorders such as depression, schizophrenia, autism are human-specific and, although attempts of animal models exist, they are limited to model only certain aspects of disease (43,44,45). Furthermore, many neurological disorders, such as multiple sclerosis, Huntington's, Parkinson's and Alzheimer's disease, have not been reported to occur spontaneously in the animal kingdom, and even their animal models fail to reproduce the main symptoms and progression of disease (46,47,48,49).…”
Section: Diseased Human Brainmentioning
confidence: 99%
“…ligand binding assay) to assess their receptor binding affinity. This step is essential to predict in-vivo efficacy of drug candidates ( Hughes et al , 2011 ; Koszła et al , 2020 ). Indeed, in-vivo efficacy is closely related to receptor site occupancy.…”
Section: Introductionmentioning
confidence: 99%